1978
DOI: 10.1038/274317a0
|View full text |Cite
|
Sign up to set email alerts
|

Mutator genes—pacemakers of evolution

Abstract: Initially a genetic oddity, male recombination in Drosophilaelanogaster is now being viewed as a means of detecting mutator activity and chromosome breakage in hybridising populations and is causing us to reconsider the source and rate at which genetic variability may be generated in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…In addition, beginning with Sturtevant (1937) others have suggested that genes which increase mutation rates in natural populations of sexual organisms will be selected against and any interference with the operation of this selection will increase the mutation rate (see discussions of this topic in Dobzhansky, 1951;Dubinin, 1964;Williams, 1966;Kimura, 1967;Leigh, 1970Leigh, , 1973Karlin and McGregor, 1974;Thompson and Woodruff, 1978;Gillespie, 1981a, l981b;Woodruff eta!., 1983). For example, hybridisation among migrants in the large-density winery population might be expected to increase mutation rates by the documented intraspecific hybrid release of mutator activity (Thompson and Woodruff, 1980;Woodruff et a!., 1980;Shaw et a!., 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, beginning with Sturtevant (1937) others have suggested that genes which increase mutation rates in natural populations of sexual organisms will be selected against and any interference with the operation of this selection will increase the mutation rate (see discussions of this topic in Dobzhansky, 1951;Dubinin, 1964;Williams, 1966;Kimura, 1967;Leigh, 1970Leigh, , 1973Karlin and McGregor, 1974;Thompson and Woodruff, 1978;Gillespie, 1981a, l981b;Woodruff eta!., 1983). For example, hybridisation among migrants in the large-density winery population might be expected to increase mutation rates by the documented intraspecific hybrid release of mutator activity (Thompson and Woodruff, 1980;Woodruff et a!., 1980;Shaw et a!., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid dysgenic mutator activity was quantified by measuring the rate of male recombination (Thompson and Woodruff, 1978). Male recombination is positively correlated with the rate of chromosome breakage and the induction of mutations attributable to movement of transposing genetic sequences (reviewed in Woodruff et aL, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Two common explanations of this socalled rare allele phenomenon have been that either hybridisation causes increased mutation rates due to the disruption of genetic suppressor systems and the release of mutator activity Table 4 Matrix correlation coefficients (Mantel test) for pairs of allele frequency difference matrices, based on pooled data. These coefficients are for descriptive purposes only because only alleles which displayed significant spatial pattern were tested against one another ( Thompson and Woodruff, 1978), or that intragenic recombination in hybrid zones produces unique alleles (Watt, 1972;Golding and Strobeck, 1983). Although contact between individuals with divergent genomes is implicit in these explanations, an increase in the frequency of rare or unique alleles imparts little information on the history of a contact zone (primary vs secondary intergradation).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Oklahoma lines carry mutator factors of the hybrid dysgenesis sytem (Thompson and Woodruff, 1978;Woodruff and Thompson, 1980). Woodruff and Thompson (1977) tested lines 1 to 25 and found all to induce male recombination in the progeny of outcrosses to the sensitive Total 1641 93 399 dp b cn bw tester strain.…”
Section: Discussior'mentioning
confidence: 99%